WS: An Approach to Linked Open Data: From Wikidata to authority files data - Nils Geißler (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
The workshop consisted of three main parts, starting with a brief introduction to Linked Open Data by recapitulating the main stages of its development and explaining some core principles and technologies. The second part focused on the approach used by the FID Philosophie to combine Wikidata and authority files. Finally, the third part was done hands-on with a Jupyter notebook in Google Colab, going through the aforementioned approach step by step using Python.